Respuesta :
Answer:
Correct choices are A and C
Step-by-step explanation:
Consider the equation
[tex]\dfrac{4}{x+6}+\dfrac{1}{x^2}=\dfrac{x+10}{x^3+6x^2}.[/tex]
Note that [tex]x\neq 0,\ x\neq-6.[/tex]
The left side of this equation is equal to
[tex]\dfrac{4}{x+6}+\dfrac{1}{x^2}=\dfrac{4\cdot x^2+1\cdot (x+6)}{(x+6)x^2}=\dfrac{4x^2+x+6}{x^3+6x^2}.[/tex]
Since the left and the right sides of this equation have the same denominators, their numerators are equal
[tex]4x^2+x+6=x+10.[/tex]
Then
[tex]4x^2=10-6,\\ \\4x^2=4,\\ \\x^2=1,\\ \\x_1=1,\ x_2=-1.[/tex]
Both these numbers are the solutions of the given equation.
Answer:
A and C is correct.
Step-by-step explanation:
[tex]\text{Rational Equation: }\frac{4}{x+6}+\frac{1}{x^2}=\frac{x+10}{x^3+6x^2}[/tex]
First we simplify this equation (-1 + x^2)/(x (6 + x))
[tex]\dfrac{x^2-1}{x(x+6)}=0[/tex]
Solution set: x=1,-1
We have to check all option which is solution of above equation.
A) x=1, we will put x=1 into equation both sides.
[tex]\text{Left Side:} \Rightarrow \frac{4}{x+6}+\frac{1}{x^2}[/tex]
[tex] \Rightarrow \frac{4}{1+6}+\frac{1}{1^2}[/tex]
[tex] \Rightarrow \frac{11}{7}[/tex]
[tex]\text{Right Side:} \Rightarrow \frac{x+10}{x^3+6x^2}[/tex]
[tex] \Rightarrow \frac{1+10}{1^3+6\times 1^2}[/tex]
[tex] \Rightarrow \frac{11}{7}[/tex]
[tex]\text{Left Side}=\text{Right Side}=\frac{11}{7}[/tex]
Thus, x=1 is a solution.
C) x=-1, we will put x=-1 into equation both sides.
[tex]\text{Left Side:} \Rightarrow \frac{4}{x+6}+\frac{1}{x^2}[/tex]
[tex] \Rightarrow \frac{4}{-1+6}+\frac{1}{(-1)^2}[/tex]
[tex] \Rightarrow \frac{9}{5}[/tex]
[tex]\text{Right Side:} \Rightarrow \frac{-1+10}{-1^3+6(-1)^2}[/tex]
[tex] \Rightarrow \frac{9}{-1+6\times 1}[/tex]
[tex] \Rightarrow \frac{9}{5}[/tex]
[tex]\text{Left Side}=\text{Right Side}= \frac{9}{5}[/tex]
Thus, x=-1 is a solution.
Thus, A and C is correct.